1995
DOI: 10.1002/bin.2360100102
|View full text |Cite
|
Sign up to set email alerts
|

Testing for spontaneous use of requests after sign language training with two severely handicapped adults

Abstract: A variety of procedures have been used to promote spontaneous requesting in persons with developmental disabilities. However, effective use of such procedures depends in part on identifying the stimuli that gained control of requests during intervention. In the present study, two adults with severe disabilities were taught to request a preferred food item with a modified gesture for “eat.” After learning to respond when the trainer held up an item, an assessment of stimulus control was conducted to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In a recent UK‐based study, 44% of teachers working in a special school reported that they have received training in Makaton whilst 99% reported using Makaton in their daily routine (Norburn, Levin, Morgan, & Harding, ). KWS has been used in practice with adults with intellectual disabilities (Meuris, Maes, & Zink, , ), and children with developmental disabilities alongside aided modes of AAC for many years (Launonen, ; Pattison & Robertson, ; Sigafoos, ). The term Makaton was used in Australia, until the term KWS was adopted in 2009 (Tan, Trembath, Bloomberg, Iacono, & Caithness, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent UK‐based study, 44% of teachers working in a special school reported that they have received training in Makaton whilst 99% reported using Makaton in their daily routine (Norburn, Levin, Morgan, & Harding, ). KWS has been used in practice with adults with intellectual disabilities (Meuris, Maes, & Zink, , ), and children with developmental disabilities alongside aided modes of AAC for many years (Launonen, ; Pattison & Robertson, ; Sigafoos, ). The term Makaton was used in Australia, until the term KWS was adopted in 2009 (Tan, Trembath, Bloomberg, Iacono, & Caithness, ).…”
Section: Introductionmentioning
confidence: 99%